A generic digital imaging and communications in medicine solution for a bidirectional interface between the modality and the radiology information system...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Smith EM; Ruffel JD; Fisher M (Journal of Digital Imaging)
The Relay is a generic Digital Imaging and Communications in Medicine (DICOM)-compliant software package. It is a bidirectional interface between the modality and the radiology information system (RIS) that uses DICOM modality worklist and modality-performed procedure step services. This device can eliminate discrepancies between patient demographic information contained in the RIS and that entered at the imaging modality. The Relay receives the worklist for a modality from the RIS. It verifies the accession number (ACC#) and medical record number (MRN) received from the RIS for a study against the ACC# and MRN entered at the modality after that study is pushed to the Relay by the modality. If the values for the ACC# and MRN contained in the image header coincide with the values stored on the RIS, the patient demographics and study protocol contained in the RIS is downloaded into the image header. The study is then automatically routed to the specified destination without technologist intervention. Images whose header does not coincide with data on the RIS are flagged for subsequent reconciliation by the technologist. When the study is completed, the Relay updates the status of the study in the RIS, if the RIS provides DICOM performed procedure step service. When required, the Relay is able to split a single study into two or more series and assign each an ACC#. Other Relay functionality includes sending studies to multiple DICOM devices, adding comments to the image header, and DICOM print service. Should the archive be unavailable to receive images for whatever reason, the Relay can store studies so image acquisition can continue without interruption or it can divert studies directly to a diagnostic workstation. This Relay provides redundancy and fault-tolerance capabilities for picture archiving and communications systems. It is vendor-independent and will function with any DICOM modality, RIS, or archive. Copyright (c) 1999 by W.B. Saunders Company